Vanek’s tumor presenting as ileocecal intussusception in an adolescent: a rare case report - Vimalesh A., Kingston; Sudamani, Sambath (International Surgery Journal, 2025)
A 17-year-old male presented with a 10-day history of abdominal pain and multiple episodes of vomiting. Clinical examination revealed tachycardia, pallor, and a mobile mass in the right iliac fossa. CT imaging showed ileo-ileal intussusception with anterior displacement of the cecum and wall thickening in the distal ileal loop. An emergency laparotomy revealed telescoping of the terminal ileum and cecum into the ascending colon, with free fluid in the pelvis. Histopathological examination confirmed Vanek’s tumor as the lead point. This case underscores the importance of considering rare pathological entities in the differential diagnosis of abdominal symptoms in adolescents.